Effectiveness of different minimally invasive epiphysiodesis techniques in the management of pediatric leg length discrepancies: a systematic review protocol. (December 2016) - Cain, Megan; Stephenson, Matthew; Umapathysivam, Kandiah; Williams, Nicole; Ianunzio, Jamie
Abstract : Review question/objective: The objective of this review is to synthesize the best available evidence on the use of percutaneous epiphysiodesis for the management of pediatric leg length discrepancies (LLDs). The effectiveness of four different percutaneous epiphysiodesis techniques will be compared, including transphyseal screws (percutaneous epiphysiodesis using transphyseal screws), physeal drilling and curettage, physeal stapling and guided growth with eight-Plates. Specific review questions to be addressed include: What method of percutaneous epiphysiodesis is most effective at achieving growth arrest and correcting a LLD in terms of:- Percentage of correction- Rate of correction Are the postoperative complication profiles different for each method of percutaneous epiphysiodesis in terms of:- Angular deformity- Failure of growth arrest- Infection- Re-operation/intervention How do children respond to each technique, specifically:- How quickly are they able to leave hospital?- How quickly do they return to activities of daily living such as schooling?